Linear arrangement of metallic and superconducting defects in a thin superconducting sample - Barba-Ortega, J.; Sardella, Edson; Albino Aguiar, J. (Elsevier, 2013)
The vortex matter in a superconducting disk with a linear configuration of metallic and superconducting defects is studied. Effects associated to the pinning (anti-pinning) force of the metallic (superconducting) defect on the vortex configuration and on the thermodynamic critical fields are analyzed in the framework of the Ginzburg Landau theory. We calculate the loop of the magnetization, vorticity and free energy curves as a function of the magnetic field for a thin disk. Due to vortex-defect attraction for a metallic defect (repulsion for a superconducting defect), the vortices always (never) are found to be sitting on the defect position. © 2013.
Keywords: Ginzburg-Landau theory; Metallic defects; Superconducting defects; Vortex matter